Switching to coformulated bictegravir, emtricitabine, and tenofovir alafenamide maintained viral suppression in adults with historical virological failures and K65N/R mutation. (January 2023) - Tsai, Mao-Song; Sun, Hsin-Yun; Chen, Cheng-Pin; Lee, Chen-Hsiang; Lee, Chun-Yuan; Liu, Chun-Eng; Tang, Hung-Jen; Hung, Tung-Che; Li, Chia-Wen; Lee, Yuan-Ti; Liou, Bo-Huang; Yang, Chia-Jui; et al.
Highlights: Reverse-transcriptase mutation K65N/R reduces the HIV susceptibility to tenofovir. Bictegravir, emtricitabine, and tenofovir alafenamide were effective as maintenance therapy in people living with HIV with archived K65N/R. The rate of experiencing viral rebound was 2.8% at week 48 of the stable switch. The presence of M184V/I plus K65N/R was not associated with viral rebound. Abstract: Objectives: Real-world experience with coformulated bictegravir, emtricitabine, and tenofovir alafenamide (BIC/FTC/TAF) is sparse as a switch regimen among people living with HIV (PLWH) having achieved viral suppression after previous virologic failures with the emergence of K65N/R. Methods: In this retrospective study, PLWH aged ≥20 years who had previous virologic failures with emergent K65N/R were included for switching to BIC/FTC/TAF after having achieved plasma HIV RNA load (PVL) <200 copies/ml for ≥3 months. PLWH were excluded if integrase inhibitor resistance-associated mutations were detected. The primary end point was losing virologic control (PVL >50 copies/ml) at week 48 using a modified US Food and Drug Administration snapshot algorithm. Results: A total of 72 PLWH with K65N/R who switched to BIC/FTC/TAF were identified. A total of 42 (59.7%) had concurrent M184V/I, and 9 (12.5%) had ≥1 thymidine analog mutations. The median duration of viral suppression was 4.7 years (interquartile range 2.3-5.8), and 97.2% (n = 70) had PVL <50 copies/ml before switching. After a median observation of 98.6 weeks (interquartile range 77.9-120.3), 94.4% (n = 68) continued BIC/FTC/TAF. At week 48, the rate of losing virologic control was 2.8% (2/72). M184V/I was not associated with viral rebound. Conclusion: Despite the emergence of K65N/R +/- M184V/I after virologic failures, BIC/FTC/TAF could be an option for simplification after viral suppression.